Advanced Cosmetic Otoplasty Art, Science, and New Clinical Techniques - Shiffman, Melvin A. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
In this book, international experts present up-to-date techniques of otoplasty in which they have extensive personal experience. Both new and modified procedures are described with the aid of a wealth of high-quality illustrations. In addition to these detailed descriptions, ear embryology and anatomy, psychological issues, postoperative care, possible risks and complications, and outcomes are extensively covered in order to provide the reader with a state of the art account of all aspects of cosmetic otoplasty. Throughout, the contributors are inventive and eloquent in guiding the reader to a better understanding that optimal results of otoplasty will be achieved only with a more refined approach than the routine use of simplified techniques. This book will be of value to both students (residents and fellows) and experienced cosmetic, plastic, maxillofacial, and general surgeons.